2019
DOI: 10.1101/630483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrophil extracellular trap stabilization leads to improved outcomes in murine models of sepsis

Abstract: Word Count: 204 Text Word Count: 4622 Figure Count: 7 Reference Count: 81 AbstractSepsis is characterized by multi-organ system dysfunction that occurs due to infection. It is associated with unacceptably high morbidity and mortality and in need of improved therapeutic intervention. Neutrophils play a crucial role in sepsis, releasing neutrophil extracellular traps (NETs) composed of DNA complexed with histones and toxic antimicrobial proteins that ensnare pathogens but also damage host tissues. At presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…A study utilizing PF4, a cationic protein released by platelets, demonstrated PF4 ability to bind to NETs and compact its structure. The neutralized NETs retained the ability to capture bacteria and improved the outcomes of sepsis in mouse models . In addition, heparin can be seen to bind to NET histones and prevent NET induced platelet aggregation .…”
Section: Polyanions That Promote Blood Coagulationmentioning
confidence: 96%
See 1 more Smart Citation
“…A study utilizing PF4, a cationic protein released by platelets, demonstrated PF4 ability to bind to NETs and compact its structure. The neutralized NETs retained the ability to capture bacteria and improved the outcomes of sepsis in mouse models . In addition, heparin can be seen to bind to NET histones and prevent NET induced platelet aggregation .…”
Section: Polyanions That Promote Blood Coagulationmentioning
confidence: 96%
“…The neutralized NETs retained the ability to capture bacteria and improved the outcomes of sepsis in mouse models. 333 In addition, heparin can be seen to bind to NET histones and prevent NET induced platelet aggregation. 255 Treatment of human septic plasma samples with protamine sulfate ex vivo has shown to decrease thrombin generation.…”
Section: Utilization Of Polyp As a Hemostatic Agentmentioning
confidence: 99%